Preliminary findings of raw bamboo curtain absorber (BCA), charred and coated bamboo ash painted characteristics for electromagnetic wave absorption / Dayang Suhaida Awang Damit - Awang Damit, Dayang Suhaida; Ahmad @ Ahmad Fauzi, Najwa Rawaida; Abbas, Mohd Hussaini; Abdullah, Hj Hasnain (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
This paper presents the preliminary findings on the utilization of bamboo, a natural material to act as Electromagnetic Wave (EMW) absorber. Bamboo curtain absorber (BCA) is a curtain or blind made from bamboo and functions to absorb the microwaves. The EMW absorption of three BCA prototypes which are Raw BCA, Charred (burned) BCA and Coated (with bamboo ash paint) BCA has been observed. The utilization of bamboo has shown significant effect in increasing the EMW absorption. The result showed the performance of the raw bamboo as a microwave absorber was very low. However, the introduction of BCA Coated (with bamboo ash paint) showed extraordinary effect to increase the EMW absorption of about 92.8% compared to raw BCA. It can be utilized as an absorbent alternative which is more economical than the existing ones in the market.